Motivation to Stay, Job Satisfaction, and Workplace Challenges Among Regular Employees Amidst the Privatization of Government-Owned Casinos - Rolando R. Calma; Percival B. Salise; Aira Mae M. Salamatin; Ken Paul M. Espinosa; Sammy Isidro P. Pagaduan; Michele G. Mendoza (Future Science / FSH-PH Publications, 2026)
With the ongoing privatization of government-owned casinos, this imperative decision to improve operations and fair-market competition for the gaming industry comes with workplace challenges that directly affect the tenured employees of the Philippine Amusement and Gaming Corporation (PAGCOR). Based on these, the quantitative-descriptive study concentrated on examining the motivation to stay, job satisfaction, and workplace challenges of the rank-and-file employees across Luzon, who were selected through stratified random sampling. The data was collected using a structured survey, which was designed to measure the intrinsic and extrinsic motivation, job satisfaction, as well as challenges (job security, career advancement, and working conditions) of the employees. Through the utilization of the Mann-Whitney U test and the Kruskal-Wallis test, the significant differences of participants demographically amongst the mentioned variables are determined. Moreover, the Pearson correlation coefficient was used to identify significant relationships between motivation to stay, job satisfaction, and employee challenges. Results revealed significant differences in workplace challenges and job satisfaction amidst the privatization. Furthermore, perceived job security and both intrinsic and extrinsic motivation were found to have been key predictors of employees’ motivation to stay. The findings suggest that transparent communication regarding retirement transition packages, job role recalibration, and enhanced performance appraisal, as well as compensation frameworks that consider the employees’ age, tenure, position, and job grade, are the most critical levers for maintaining workforce stability, motivation, and retention. These insights could guide PAGCOR and policymakers in formulating employee-centered strategies that mitigate the adverse effects of organizational change and sustain employee engagement.